Implicit Approximate Crank–Nicolson Theory for Anisotropic Ferrite Structure Simulation with Enhanced Absorption (Adv. Theory Simul. 11/2021). Issue 11 (8th November 2021) - Wu, Peiyu; Xie, Yongjun; Jiang, Haolin; Di, Hanyi; Natsuki, Toshiaki
Abstract : Large Magnetoresistance in Scandium Nitride Magnetic Tunnel Junctions Theory and simulation are essential to discovering new materials for computing. In article number 2100309, Jean Anne Incorvia, Suyogya Karki, Vivian Rogers, and co‐workers identify scandium nitride as a tunnel barrier material and compare its properties to state‐of‐the‐art magnesium oxide. The results show a high magnetoresistance with low wavefunction decay rates, suggesting scandium nitride could be used for magnetic tunnel junction‐based spintronic devices.